Epigenetic modulation of FBW7/Mcl-1 pathway for lung cancer therapy. Issue 1 (2nd January 2021) - Kim, Mi Jeong; Chen, Guo; Sica, Gabriel L.; Deng, Xingming
ABSTRACT: Methylation induces epigenetic silencing of tumor suppressor genes in human lung cancer. Inhibition of DNA methyltransferases by decitabine (DAC) can demethylate and activate epigenetically silenced tumor suppressor genes. Epigenetic therapy using DAC should be an attractive strategy for lung cancer therapy. FBW7 is a tumor suppressor that functions as an Mcl-1 E3 ligase to degrade Mcl-1 by ubiquitination. Here we discovered that treatment of various human lung cancer cells with DAC resulted in activation of FBW7 expression, decreased levels of Mcl-1 protein, and growth inhibition. DAC-activated FBW7 expression promoted Mcl-1 ubiquitination and degradation leading to a significant reduction in the half-life of Mcl-1 protein. Mechanistically, treatment of lung cancer cells or lung cancer xenografts with DAC induced the conversion of the FBW7 gene from a methylated form to an unmethylated form, which was associated with the increased expression of FBW7 and decreased expression of Mcl-1 in vitro and in vivo . DAC suppressed lung cancer growth in a dose-dependent manner in vivo . Combined treatment with DAC and a Bcl2 inhibitor, venetoclax, exhibited strong synergistic potency against lung cancer without normal tissue toxicity. These findings uncover a novel mechanism by which DAC suppresses tumor growth by targeting the FBW7/Mcl-1 signaling pathway. Combination of DAC with Bcl2 inhibitor venetoclax provides more effective epigenetic therapy for lung cancer.